Development Student Worksheet in the Topic of Regular Circular Motion with Blended Learning based Edmodo as Learning Motivations for Student - Susilawati, Susilawati; Ishafit, Ishafit; Setyawati, Eni (Indonesian Review of Physics (IRiP), 2019)
The research aims to develop learners ' worksheets on the subject of circular motion with the Edmodo based blended Learning as well as the motivation to learn learners. The test subjects in this study were vocational school grade ofÂ  X students. The model used is the ADDIE development model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. To know the feasibility of media validation. To know the feasibility of media done validation. This validation is in the form of a poll with predefined criteria and indicators. From the development of student worksheet conducted an expert test of materials, media experts and users with a percentage of 79.68%, 77.27% and 83.62% with that percentage, then the student worksheet with blended learning based Edmodo As the motivation to learn learners in the categorized worthy as a learning media.